Yield and Forage Quality on Native Meadows as Affected by Burn and Fertilization Management - Junior I. Yasuoka; Dale Helwig; Walter H. Fick; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
Native meadows are widely used by producers in southeast Kansas. However, there are few studies about management practices to improve agronomic performance in southeast Kansas. This study evaluated the spring burn effect combined with the application of lime, nitrogen, phosphorus, and potassium on yield and forage quality in native meadows. Yield and forage quality on native meadows were not affected by lime application, or P and K fertilization in the first year of the study. However, N fertilization increased yield, crude protein, and total digestible nutrients when associated with spring burn.
Keywords: biomass; management; hay production; fertilization